TANGGAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays L. Saccharata) PADA APLIKASI BERBAGAI PUPUK ORGANIK - Pasta,Andi Ette , Henry N. Barus, Ikhwana (AGROTEKBIS, 2015)
The research was conducted in the Green house the Faculty of Agriculture, University of  Tadulako Palu. Time of the study began in May   2014. This study used completely randomized design with 5 treatments namely A : Without Fertilizer (control), B : Manure Fertilizer (20 ton ha-1), C : Bokasi Fertilizer (20 ton ha-1), D : Biofertilizer (33,3 ton ha-1), and E : Inorganic Fertilizer (NPK 350 kg ha-1). Each treatment was repeated 4 times resulted to 20 experimental units. Treatment which shows significancy will be further tested with honestly significant difference (HSD) at level of 5%. The results showed that the growth and yield of corn treated with various organic fertilizers positively impacted on plant height, number of leaves, flowering time, cob weight (with husk and without husk) and cob length (with husk and without husk). The application of biofertilizers (microbial from bamboo grove) resulted to better growth and yield.